The use of radiofrequency for hepatocellular carcinoma ablation : an update review and perspectives - Monteiro, Melissa Silva (2017)
The World Health Organization classifies liver cancer among the five types of cancer with highest death rates in the world. Among the current methods available for the treatment of liver cancer, there is the resection of hepatic tissue and the radiofrequency ablation of the tumor. Even though resection presents the best results, only 10% to 15% of the affected patients may eligible for this procedure. On the other hand, the radiofrequency ablation encompasses a larger scope of patients and provides a non-invasive method when compared to resection. There is research with sufficient evidence to allow the transposition of this concept to new technological paradigms, which would yield a more effective ablation process, i.e.: generating enough volumetric necrosis for complete regression of the tumor, leading to a high survival rate of patients. These technological paradigms encompass aspects of operability, innovation and of theoretical framework. In terms of operability, there is the use of better imaging sources to aid the healthcare professional in the positioning of electrodes; in terms of innovation, there are new technologies such as the use of optical fiber microsensors and metallic magnetic nanoparticles to increase the efficiency of the process; in terms of theoretical framework, there is the development of more precise mathematical models that would expand the possibilities of application and increase its effectiveness. These new challenges are new possibilities that may reshape the concept and the use of radiofrequency ablation as it is currently known.